Foreign Experience of Child Violence Prevention in General Education Institutions - Karimova Maftuna Karimberdiyevna (Peerian Journals Publishing, 2023)
In this article, the policies and adopted laws of foreign countries in the effective organization of the general, special, prevention of crimes on the effective prevention of harassment and violence in the family, as well as other organizations that carry out activities on the protection of the legal interests of the child, are supported by the state. is stated to be supported
Keywords: UN; UNICEF; violence